A high‐gain compact circularly polarized microstrip array antenna with simplified feed network. Issue 12 (13th September 2019) - Zou, Yanlin; Li, Haojie; Xue, Yuxiao; Sun, Baohua
Abstract: A broadband high‐gain circularly polarized (CP) microstrip antenna operating in X band is proposed. The circular polarization property is achieved by rotating four narrow band linearly polarized (LP) microstrip patch elements in sequence. Since the conventional series‐parallel feed network is not conducive to the miniaturization of the array, a corresponding simplified feed network is designed to realize the four‐way equal power division and sequential 90° phase shift. With this feed network, the impedance bandwidth (IBW) of the CP array is greatly improved compared with that of the LP element, while maintaining a miniaturized size. Then, parasitic patches are introduced to enhance the axial ratio bandwidth (ARBW). A prototype of this antenna is fabricated and tested. The size of proposed antenna is 0.93 λ 0 × 0.93 λ 0 × 0.017 λ 0 ( λ 0 denotes the space wavelength corresponding to the center frequency 10.4 GHz). The measured 10‐dB IBW and 3‐dB ARBW are 13.6% (9.8‐11.23 GHz), 11.2% (9.9‐11.07 GHz) respectively, and peak gain in the overlapping band is 9.8 dBi.